RAJAH DALAM TRADISI MASYARAKAT ACEH - utami, Rizka; Auliana, Nisa (Universitas Islam Negeri Antasari Banjarmasin, 2024)
Abstract: Some people in Aceh believe that there are individuals who possess the ability to call upon guardian spirits or khadam that protect them. This is known as